The Effect of Debt To Asset Ratio, Long Term Debt To Equity Ratio and Time Interest Earned Ratio on Profitability - Farah, Indina; Amin, Chaerul; Pramudianto, Pramudianto (Bina Bangsa International Journal of Business and Management, 2021)
This study’s purpose is to analyse the influence of DAR, LDER, and TIER on Profitability. Populations of data are taken food and beverage companies listed in BEI from 2009-2011. Samples taken using purposive sampling method and total of samples used during study period is 39 samples. Hypothesis used in this study is multiple linear regression. Based on F test, the results indicated DAR, LDER, and TIER have a significant effect on Profitability. DAR, LDER, and TIER partial effect on Profitability was evaluated using T test. DAR have a negative and non-significant effect on ROE at -0,252. LDER have a negative and significant effect on ROE at -0,437 and TIER have a positive but non-significant effect on ROE at 0,00020